Characterisation of a soft X-ray optimised CMOS Image Sensor. (1st May 2022) - Heymes, J.; Ivory, J.; Stefanov, K.; Buggey, T.; Hetherington, O.; Soman, M.; Holland, A.
Abstract: A prototype CMOS Image Sensor optimised for soft X-ray applications has been designed by the Centre for Electronic Imaging in partnership with Teledyne-e2v. The device features four different pixel variants (three variants of 40 μm pitch pixels, and one variant of 10 μm pixels) each covering a quarter of the 2 × 2 cm 2 image area. The pixel designs feature fully depleted pinned photodiodes using reverse substrate bias and have been optimised for low noise operation, high responsivity and low image lag. The fabricated front-illuminated devices have been tested in a custom-built vacuum test setup at operating temperatures between -30°C and -40°C. The sensors feature less than 5 e - RMS readout noise and energy resolution of 142 eV at Mn-K α (5.9 keV). The response to soft X-ray with different sensor parameters (e.g. pixel pitch, deep-depletion extension implant depth, and back-bias voltage) is also studied.